How Are We Educating Future Physicians and Pharmacists in Pakistan? A Survey of the Medical and Pharmacy Student’s Perception on Learning and Preparedness to Assume Future Roles in Antibiotic Use and Resistance - Mubarak, Naeem; Arif, Sara; Irshad, Mahnoor; Aqeel, Rana Muhammad; Khalid, Ayesha; Ijaz, Umm e Barirah; Mahmood, Khalid; Jamshed, Shazia; Zin, Che Suraya; Saif-ur-Rehman, Nasira (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Abstract: Background: Medical and pharmacy students are future healthcare professionals who will be on the forefront in dealing with antibiotics in hospitals or community settings. Whether the current medical and pharmacy education in Pakistan prepares students to take future roles in antibiotic use remains an under-researched area. Aim: This study aims to compare medical and pharmacy students’ perceived preparedness, learning practices and usefulness of the education and training on antibiotic use and resistance imparted during undergraduate studies in Pakistan. Design and Setting: It was amulti-centre cross-sectional survey of medical and pharmacy colleges in Punjab, Pakistan. Method: A self-administered questionnaire was used to collect data from final year medical and pharmacy students. Descriptive statistics were used for categorical variables while independent t-test and One-way ANOVA computed group differences. Result: Nine hundred fortyeight respondents (526 medical and 422 pharmacy students) completed the survey from 26 medical and 19 pharmacy colleges. Majority (76.1%) of the pharmacy students had not completed a clinical rotation in infectious diseases. The top three most often used sources of learning antibiotic use and resistance were the same among the medical and the pharmacy students; included textbooks, Wikipedia, and smart phone apps. Overall self-perceived preparedness scores showed no significant difference between pharmacy and medical students.. The least prepared areas by medical and pharmacy students included transition from intravenous to oral antibiotics and interpretation of antibiograms. Both medical and pharmacy students found problem solving sessions attended by a small group of students to be the most useful (very useful) teaching methodology to learn antibiotic use and resistance. Conclusions: Differences exist between medical and pharmacy students in educational resources used, topics covered during undergraduate degree. To curb the growing antibiotic misuse and resistance, the concerned authorities should undertake targeted educational reforms to ensure that future physicians and pharmacists can play a pivotal role in rationalizing the use of antibiotics.